2000
DOI: 10.1016/s0921-4488(00)00125-5
|View full text |Cite
|
Sign up to set email alerts
|

Bioserogroups of Campylobacter species isolated from sheep in Kaduna State, Nigeria

Abstract: Sheep Campylobacter isolates from Kaduna State were characterized into their species and bioserogrouped. A total of 1100 samples were collected from Kaduna abattoir and National Animal Production Research Institute (NAPRI), Shika. The samples were from 250 gallbladder, 250 intestinal contents, 100 fetal stomach contents all from Kaduna abattoir while 250 rectal swabs and 250 vaginal swabs were from the NAPRI Small Ruminant Programme. Of a total of 1100 samples, 39 (3.54%) yielded Campylobacter organisms. The h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 17 publications
1
9
1
3
Order By: Relevance
“…However, the presence of Campylobacter on lamb after chilling has been considered to be low (Miller and Mandrell 2005). Similarities between documented human Campylobacter isolates in Nigeria and those from sheep were found in a study conducted by Raji et al. (2000) in raising the possibility of cross‐contamination between sheep and man.…”
Section: Introductionsupporting
confidence: 63%
“…However, the presence of Campylobacter on lamb after chilling has been considered to be low (Miller and Mandrell 2005). Similarities between documented human Campylobacter isolates in Nigeria and those from sheep were found in a study conducted by Raji et al. (2000) in raising the possibility of cross‐contamination between sheep and man.…”
Section: Introductionsupporting
confidence: 63%
“…A higher prevalence rate (17.5%) was reported for cecal samples from sheep from Swiss abattoirs, with only C. jejuni and C. coli being detected (342). In both studies, C. jejuni was the major Campylobacter species detected (341,342). Screening of fecal samples from 222 dairy goats on 12 farms in Spain failed to detect any Campylobacter species (343).…”
Section: Domesticated Animalsmentioning
confidence: 65%
“…In Nigeria, 6.8% of intestinal samples from sheep were found to be positive for C. jejuni, C. coli, or C. lari (341). A higher prevalence rate (17.5%) was reported for cecal samples from sheep from Swiss abattoirs, with only C. jejuni and C. coli being detected (342).…”
Section: Domesticated Animalsmentioning
confidence: 96%
“…Many other studies also indicated the association of Campylobacter diarrhea with the consumption of contaminated water or foods, ownership of livestock or poultry, or contact with animals [15]. Domestic birds and companion animals are known as reservoirs for Campylobacter species, and shedding of the bacteria from these reservoirs causes contamination of the environment [20][21][22]. Strains isolated from human and chickens were phenotypically and genotypically similar, confirming that chickens are an important source of human Campylobacteriosis in developing countries [20,23].…”
Section: Discussionmentioning
confidence: 96%